Platform Mergers: Lessons from a Case in the Digital TV Market. (26th March 2022) - Ivaldi, Marc; Zhang, Jiekai
Abstract : We contribute to the analysis of mergers in two‐sided markets, in which a platform provides its service for free on one side but obtains all its revenues from the other. A structural model allowing for multi‐homing of advertisers is developed to assess a decision of the French competition authority, which approves the merger of the broadcasting services of TV channels but prohibits the merger of their advertising sales services through a behavioral remedy. We show that ignoring the interaction between the two sides of platforms in designing competition or regulatory policy can result in unexpected outcomes.